Max Weber : selections in translation - Weber, Max, 1864-1920, (Cambridge University Press, 1978)
In this volume, Mr Runciman has selected extracts, from Max Weber's writings which reflect the full range of his major concerns: the nature of domination in human society, the role of ideas in history, the social determinants of religion, the origin and impact of industrial capitalism and the scope and limits of social science itself. He has also included some shorter extracts from Weber's less familiar writings on such diverse topics as the stock exchange and the history of the piano.